Initial human experience of endoscopic ultrasound-guided photodynamic therapy with a novel photosensitizer and a flexible laser-light catheter - Choi, Jun-Ho; Oh, Dongwook; Lee, Jae Hoon; Park, Jin-hong; Kim, Kyu-pyo; Lee, Seung Soo; Lee, Young-Joo; Lim, Young-Suk; Song, Tae Jun; Lee, Sang Soo; Seo, Dong-Wan; Lee, Sung Koo; Kim, Myung-Hwan; Park, Do Hyun (Endoscopy, 2015)
Background and study aims: New methods for the endoscopic selective ablation of locally advanced pancreaticobiliary malignancies as a minimally invasive approach are needed. Our aim was to examine the feasibility and safety of endoscopic ultrasonography (EUS)-guided photodynamic therapy (PDT) for local tumor control in patients with locally advanced pancreaticobiliary malignancies.Patients and methods: A chlorin e6 derivative and a flexible laser-light catheter were used to perform EUS-guided PDT in four patients with locally advanced pancreaticobiliary malignancies.Results: EUS-guided PDT was technically feasible in all four patients with locally advanced pancreaticobiliary malignancies (two in the caudate lobe of the liver, one in the far distal bile duct, and one in the tail of the pancreas). No treatment-related complications occurred. The median volume of necrosis produced by PDT was 4.0 cm3 (range 0.7 – 11.3). Disease remained stable in all four patients during a median follow-up of 5 months (range 3 – 7).Conclusion: These preliminary data suggest that EUS-guided PDT with a second-generation photosensitizer and a flexible laser probe is feasible and safe.